Efficient Grocery Shopping Using Geolocation and Data Mining - Aliaga-Vasquez, Myrella (2022)
In the current pandemic, people are looking to leave their houses less frequently to prevent getting infected, but the absence of an app that shows the necessary information before going to the supermarket forces people to look in different supermarkets for the products they want to buy, thus increasing their chances of catching the virus, not to mention the waste of money and time. DoremyS is an app that allows you to create shopping lists that indicate to the user which supermarket to visit to find every product in them; it uses Geolocation to recommend supermarkets that are near the user and Data Mining to recommend shopping lists based on the user's interests.